Technical Guidance for Increasing Production of Cow Manure-Based Organic Fertilizer in Farmer's Groups in Konda District - Hafid, Harapin; Midranesiah; Ananda, Siti Hadrayanti (Journal of Saintech Transfer, 2022)
This technical guidance activity aims to teach how to process organic fertilizer based on cow dung which is mostly produced by the community's livestock, so that it canÂ  reduce the cost of inorganic fertilizer and be more profitable. This activity was carried out in farmer groups in Morome and Alebo Villages, Konda District, South Konawe Regency. The method of activity is carried out by: (1) lectures and discussions on materials and methods of processing organic fertilizers, (2) demonstrations and guidance on theÂ  selection of materials and processing of cow dung-based organic fertilizers, (3) packaging and marketing methods for livestock manure-based organic fertilizers. cow. The counseling material presented received a positive and satisfactory response from the participants. In general the participants wanted to adopt the training materials and were very active in the technical guidance. It was concluded that the participants were very interested in applying the guidance materials taught and producing them commercially. The participants hoped that their village would often be given agricultural and livestock guidance and counseling activities.